2002
DOI: 10.1177/0018726702055008178
|View full text |Cite
|
Sign up to set email alerts
|

The Dialogue between the ‘Self’ and the ‘Other’: A Process Analysis of Palestinian-Jewish Encounters in Israel

Abstract: This study assumes that the collective identities of both Jews and Palestinians in Israel have long been constructed around the Jewish-Palestinian conflict, a major focus of social and historical reality in the Middle East region. Monolithic in their early stages, these constructions of identity underwent a process of deconstruction and reconstruction, primarily due to changes in the political reality (the peace process), globalization, and the surfacing of conflicts that were hidden within the monolithic cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 21 publications
4
47
0
Order By: Relevance
“…Such non-critical approaches to dialogue generally produce benefits mostly for the members of privileged groups and reinforce the tokenizing role of less privileged groups. For example, dialogues that emphasize interpersonal dynamics to the exclusion of socio-political analysis can focus just on creating harmony between groups, rather than on analyzing and working with conflicts between groups (Abu-Nimer 1999; Maoz et al 2002).…”
Section: Emerging Criticismsmentioning
confidence: 99%
“…Such non-critical approaches to dialogue generally produce benefits mostly for the members of privileged groups and reinforce the tokenizing role of less privileged groups. For example, dialogues that emphasize interpersonal dynamics to the exclusion of socio-political analysis can focus just on creating harmony between groups, rather than on analyzing and working with conflicts between groups (Abu-Nimer 1999; Maoz et al 2002).…”
Section: Emerging Criticismsmentioning
confidence: 99%
“…Nagda and Zúñiga (2003), for example, found that the more students valued dialogic learning-sharing, colearning, inquiry, conflict exploration, and action planning-the more positive their learning outcomes, which may also be reflected in the quantity and quality of participation (Maoz, 2001;Maoz, Steinberg, Bar-On, and Fakhereldeen, 2002). For instance, storytelling and personal sharing in intimate interactions appear to foster comfort in interracial and interethnic situations, learning from diverse peers, reduction in unconscious prejudice, and capacity for leadership in a diverse democracy (Vasques-Scalera, 1999;Werkmeister-Rozas, 2004;Yeakley, 1998).…”
Section: Educational Designmentioning
confidence: 99%
“…Our design and analysis moves beyond the individual as unit of analysis to consider the dialog process itself. Our study thus adds to a growing literature documenting the process of intergroup contact, particularly within the context of the Israeli-Palestinian conflict (e.g., Abu-Nimer, 1999;Bekerman, 2002;Helman, 2002;Maoz, 2000b;Maoz et al, 2002Maoz et al, , 2004. Given that the structural conditions that create conflict and prejudice rely upon narratives for maintenance, meaning, and adherence, it stands to reason the research that can directly study narratives as they are deployed in interaction is needed.…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 94%
“…Following a similar epistemological and methodological approach to other research on existing intergroup encounters in the field (e.g., Bekerman, 2002;Helman, 2002;Maoz et al, 2002;Maoz, Bar-On, Bekerman, & Jaber-Massawa, 2004), we employed an inductive, hermeneutic strategy in which the goal was to describe actual dialogic content as it emerged. Unique to our study, however, was an experimental design that allowed us to examine variability in dialog content based on the way in emerged across different facilitation models (coexistence versus confrontational) and topics (history versus future).…”
Section: Current Studymentioning
confidence: 99%